2009
DOI: 10.1162/jocn.2009.21008
|View full text |Cite
|
Sign up to set email alerts
|

Two Types of Action Error: Electrophysiological Evidence for Separable Inhibitory and Sustained Attention Neural Mechanisms Producing Error on Go/No-go Tasks

Abstract: Abstract& Disentangling the component processes that contribute to human executive control is a key challenge for cognitive neuroscience. Here, we employ event-related potentials to provide electrophysiological evidence that action errors during a go/ no-go task can result either from sustained attention failures or from failures of response inhibition, and that these two processes are temporally and physiologically dissociable, although the behavioral error-a nonintended response-is the same. Thirteen right-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 40 publications
5
78
2
1
Order By: Relevance
“…Errors of commission may be taken as evidence of failures in both sustained attention and response inhibition (O'Connell et al, 2008). Previous research has indicated that lowered noradrenaline levels may lead to decreased ability to inhibit inappropriate responses (Chamberlain, Muller, Blackwell, Clark, Robbins & Sahakian, 2006;Eagle, Bari & Robbins, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Errors of commission may be taken as evidence of failures in both sustained attention and response inhibition (O'Connell et al, 2008). Previous research has indicated that lowered noradrenaline levels may lead to decreased ability to inhibit inappropriate responses (Chamberlain, Muller, Blackwell, Clark, Robbins & Sahakian, 2006;Eagle, Bari & Robbins, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Though it has a response inhibition component, it has been validated as a sensitive measure of sustained attention in EEG, fMRI and behavioural studies (Fassbender et al, 2004;Johnson, Kelly, Bellgrove, Barry, Cox, Gill et al, 2007;O'Connell, Dockree, Bellgrove, Turin, Ward, Foxe et al, 2008). Single white digits between 1 and 9 were presented on a black screen in a variety of font sizes for a period of 250ms, followed a 900ms mask consisting of a white X in a circle that appeared to 'flash'.…”
Section: Sustained Attention To Response Task (Sart)mentioning
confidence: 99%
“…This method allows to estimate inverse solutions for action monitoring potentials, when unwanted activities (i.e., the motor execution stage involving motor cortex regions and the feedback processing stage involving visual cortex regions) common to all conditions have been removed from the analysis and hence do not strongly bias the outcome in any direction (either motor or visual cortex; see Yeung et al, 2004;Vocat et al, 2008;Koban et al, 2010 for similar approaches). We used a standard four-shell ellipsoidal head model approximation (Scherg, 1990) registered to human brain atlas of Talairach & Tournoux (Talairach and Tournoux, 1988), that has already been used in previous error monitoring ERP studies (Dehaene et al, 1994;Herrmann et al, 2004;O'Connell et al, 2007;Vocat et al, 2008;O'Connell et al, 2009). Similar to ERP mean amplitudes measures, we used time windows of -10 to +10 ms around each peak for dipole analysis.…”
Section: Source Analysismentioning
confidence: 99%
“…They then completed a go/no-go task, also known as a sustained attention to response test. The task was closely modelled after that used in prior studies with a random presentation of "go" and "no go" trials (O'Connell et al, 2009). …”
Section: Methodsmentioning
confidence: 99%